2020
DOI: 10.3390/pharmaceutics12020150
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an in-line API Quantification Method Using AQbD Principles Based on UV-Vis Spectroscopy to Monitor and Optimise Continuous Hot Melt Extrusion Process

Abstract: A key principle of developing a new medicine is that quality should be built in, with a thorough understanding of the product and the manufacturing process supported by appropriate process controls. Quality by design principles that have been established for the development of drug products/substances can equally be applied to the development of analytical procedures. This paper presents the development and validation of a quantitative method to predict the concentration of piroxicam in Kollidon® VA 64 during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Almeida et al [ 35 ] monitored and optimised the concentration of piroxicam (PRX) in Kollidon ® VA 64 using in-line UV–Vis coupled with PLS. They developed one calibration model and two validation data sets; all three data sets (calibration and validation sets) included data from extrusion runs performed on different days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almeida et al [ 35 ] monitored and optimised the concentration of piroxicam (PRX) in Kollidon ® VA 64 using in-line UV–Vis coupled with PLS. They developed one calibration model and two validation data sets; all three data sets (calibration and validation sets) included data from extrusion runs performed on different days.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2004, many research studies have been reported, in which different machine learning algorithms have been applied to in-process data to analyse product and process parameters in real-time. The applications include the monitoring of product critical quality attributes (CQAs), including the following: the solid state of the polymer/drug [ 2 , 3 ]; API/additive concentration [ 34 , 35 ]; degradation of the polymer [ 36 , 37 ]; the particle size of additive/s [ 31 ]; and mechanical properties [ 33 ]. Other works have examined the monitoring of critical process properties (CPPs), including melt temperature [ 38 ], pressure [ 39 ], and viscosity [ 40 ], and for process fault detection [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most commonly used PAT tools include UV-Vis ( 139 , 140 ), Fourier transform near-infrared (FT-NIR) ( 104 , 119 ), and Raman ( 141 , 142 ) spectroscopy techniques. These techniques are simple, fast, and non-destructive to the samples during the HME process.…”
Section: Recent Innovations In Hot-melt Extrusion To Prevent Thermal mentioning
confidence: 99%
“…A further study on the use of UV-Vis for measuring API concentration in the polymer and API content uniformity was carried out. Analytical models based on the UV-Vis spectra obtained during the HME process were developed as a quantitative method to predict the concentration and content uniformity of piroxicam in Kollidon® VA 64 ( 139 ). The study by Haser et al showed the possibility of in-line monitoring of the solubilization of meloxicam using a UV probe positioned at the die ( 149 ).…”
Section: Recent Innovations In Hot-melt Extrusion To Prevent Thermal mentioning
confidence: 99%
“…To reduce the CV effort, HME would greatly benefit from in-line processes that assess the cleanliness of the material and equipment. Although ultraviolet-visible (UV–Vis) spectroscopy has been shown to be highly applicable to in-line analyses in HME [ 26 , 27 , 28 , 29 , 30 ], e.g., for monitoring the API content [ 30 ], to date no scientific study has employed UV–Vis spectroscopy to detect the API in terms of cleanliness of a material and/or processing equipment. In addition, it is not certain, if an API-free material that is mainly analysed by in-line techniques such as UV–Vis spectroscopy, can also represent an API-free processing equipment [ 9 ], since contaminated material might be trapped in dead spots of the equipment [ 31 ] and contribute to cross-contamination.…”
Section: Introductionmentioning
confidence: 99%